Given that:
a1=27, an=(an-1)+4
the second term will be:
a2=a1+4
a2=27+4=31
The explicit formula for arithmetic sequence is given by:
an=a+(n-1)d
where:
a= first term
d=common difference
n=nth term
from the information given:
a=27
d=31-27=4
thus the explicit formula will be:
an=27+(n-1)4
an=27+4n-4
an=23+4n
Answer: an=23+4n
Answer:
![\sqrt{8}=2\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B8%7D%3D2%5Csqrt%7B2%7D)
Step-by-step explanation:
by using well known formula, distance on XOY plane
![\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\=\sqrt{(-8-(-6))^2+(6-4)^2}\\=\sqrt{(-2)^2+(2)^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%28x_2-x_1%29%5E2%2B%28y_2-y_1%29%5E2%7D%5C%5C%3D%5Csqrt%7B%28-8-%28-6%29%29%5E2%2B%286-4%29%5E2%7D%3C%2Fp%3E%3Cp%3E%5C%5C%3D%5Csqrt%7B%28-2%29%5E2%2B%282%29%5E2%7D)
Answer:
No, a reasonable estimate is around 6 times $7 = $42
Step-by-step explanation:
$6.99 is rounded up to 7, and there are 6 people who ordered a $7 meal. And 6 times 7 is 42
42 rhhrhjejrjfitkkrjrjrhrt